Short sleep time may be the main reason for irregular breakfast to cause overweight—a cross-sectional study - Yang, Wei; Zhuang, Zhao; Huang, Pengxiang; Zhang, Man; Wang, Kebo; Jiang, Ying; Zhou, Han; Yu, Lianlong (Frontiers in Nutrition, 2024)
In recent years, the relationship between circadian rhythm and overweight and obesity has attracted the attention of many scholars. To evaluate association between the duration of sleep and the regularity of breakfast and overweight. A total of 1178 students from Qingdao University were selected by stratified cluster sampling. There were 601 males (24.69±0.80 years old) and 569 females (24.54±0.70 years old). We used body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) to define overweight levels. Chi-square test, Pearson correlation test, and logistic regression were applied to test association among overweight, sleep duration, sleep onset time, and breakfast regularity. Pittsburgh sleep quality index was used to assess the overall sleep quality of the study subjects. Mediation effect and Sobel test were used to analyze the effect of sleep duration on breakfast regularity and overweight. Only 34.1% of the population ate breakfast every day, and eating breakfast 1-3 times per week was associated with a higher risk of overweight (